Transformational Leadership in Islamic Education Management for Building a Quality Culture in an Era of Change - Mohammad Adnan; Patsun Patsun; Wan Mariah; Ahmad Faqih Udin; Syamsuddin Syamsuddin (Journal of Innovative and Creativity (Joecy), 2026)
Transformational leadership has become increasingly important in Islamic education management as educational institutions face rapid technological, social, organizational, and policy changes. This study aims to examine the role of transformational leadership in developing a quality culture within Islamic educational institutions and to identify strategic approaches for strengthening institutional adaptability in an era of change. This study employs a library research approach by critically reviewing relevant scholarly literature, including books, peer-reviewed journal articles, and conceptual studies addressing transformational leadership, Islamic education management, organizational culture, and educational quality. The findings indicate that transformational leadership provides an important managerial foundation for developing a sustainable quality culture through shared vision, inspirational motivation, intellectual stimulation, individualized consideration, participatory decision-making, and continuous professional development. The study further reveals that the integration of Islamic values, including trustworthiness, responsibility, justice, consultation, and exemplary conduct, strengthens the ethical dimension of transformational leadership. Such leadership contributes to collaborative organizational relationships, innovation, staff empowerment, continuous improvement, and institutional responsiveness to environmental changes. Therefore, transformational leadership should not be understood merely as an administrative leadership model but as a strategic mechanism for integrating organizational transformation with Islamic educational values. The study concludes that strengthening transformational leadership can support the development of adaptive, ethical, collaborative, and quality-oriented Islamic educational institutions.